PPAR-gamma Signaling in Metabolic Homeostasis - Rina Triana; Nurrani Mustika Dewi; Siska Darmayanti; Eka Herawati; Maria Novalentina; Made Putra Semadhi; Miftakh Nur Rahman (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Peroxisome proliferator-activated receptor (PPAR)-γ, or also known as nuclear receptor subfamily 1 group C member 3 (NR1C3), is a PPAR which serves as master regulator of adipocytes differentiation, and plays an important role in lipid metabolism or adipogenesis. Recent study showed that PPAR-γ is expressed in most tissue and also has critical impact in many metabolic homeostasis disorders.CONTENT: Dysregulation of PPAR-γ is correlated to the development of obesity, type 2 diabetes, atherosclerosis, cardiovascular disease, acute kidney injury, autoimmune disease, gastrointestinal disease and Alzheimer’s disease. Abundant number of new emerging compounds, with in vitro and in vivo effectiveness as natural and synthetic agonists of PPARs, are investigated, developed and used as the treatment of metabolic disorders of glucose and/or lipid and other diseases.SUMMARY: Based on all studies explanation, targeting PPAR-γ is proven to be a good therapeutic method for reducing negative effect of several metabolic homeostasis disorder. Now, many natural and synthetic agonists of PPARs are used as the treatment of metabolic disorders of glucose and/or lipid or another metabolic homeostasis disorder. Such agonists have different properties and specificities for individual PPARs receptors, different absorption and distribution, and distinctive gene expression profiles, which ultimately lead to different clinical outcomes.KEYWORDS: PPAR-γ, dysregulation, agonist, adipogenesis, metabolic disorder, homeostasis